PENERAPAN KESANTUNAN DALAM PERCAKAPAN BERBAHASA INGGRIS ONLINE DENGAN PENUTUR ASING MELALUI SYNCHRONOUS MEDIA - Wahyunengsih Wahyunengsih; Avita Ayu Permana Sari (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2021)
The development of the digital world provides opportunities for students to communicate directly with foreigners from various parts of the world. This study focuses on analyzing the application of ethical manners by students of Islamic universityy in Indonesia in English conversations through synchronous social media with foreign speakers. The aim is to determine the form of application of courtesy ethics in conversations in English with foreign speakers by Islamic university students. The results of this study are expected to be a recomendation for educators and students themselves in improving education and the application of ethical manners in English as international language. Given that Islamic University students are one of the well-educated ambassadors of the Islamic community in the international world. The subjects of this study involved 30 students of the Syarif Hidayatullah Islamic University Jakarta. Students have conversations with foreign speakers using the Ome TV and Zoom Meeting application which is carried out naturally. Qualitative descriptive research method is used to obtain data in this study. This study finds several patterns of ethical application of courtesy by students which are discussed in terms of ethical principles in speaking basically based on six maxim of politeness by Leech. The results of this study also provide ethical recommendations for English conversation to Islamic university students as social media users. In addition, it is also hoped that it will become a reference for teachers to always provide language education that has ethical values ​​of politeness that can be accepted by all communities worldwide.